Peran UTAUT2 dalam Membentuk Behavioral Intention pada Pengguna Tokopedia di Kalangan Generasi Z - Solihin, Dede; Furyanah, Anah (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the role of the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model in forming behavioral intention in Tokopedia application users among Generation Z. Generation Z is a group that is very familiar with digital technology and is the main target in the e-commerce market in Indonesia. This study uses a quantitative approach with a survey method. Data were collected from 130 respondents aged 18–25 years who are active Tokopedia users. Data analysis was carried out using the Structural Equation Modeling (SEM) method to test the influence of UTAUT2 variables, namely performance expectancy, effort expectancy, social influence, and facilitating conditions on behavioral intention. The results showed that the four variables had a positive and significant effect on behavioral intention. These findings indicate that perceptions of performance, ease of use, social support, and availability of facilities greatly determine Generation Z's intention to use Tokopedia. This study contributes to the development of e-commerce strategies that are more effective and relevant to the characteristics and needs of the young digital generation.